Determinants of Financial Performance and its Impact on the Growth of Islamic Bank Assets on Indonesia - Salim, M Noor; Djausin, R Pandji Ibnul (International Journal of Business, Economics and Management, 2020)
This study aims to examine and analyze the determinant of financial performance (return on assets), namely intellectual capital that consist of human capital, structural capital, capital employed and good corporate governance (GCG) that consist of board size and board of demography and its impact on the growth of Islamic banks assets in Indonesia for the period 2014 – 2018. Research data is annual report and GCG report of 12 Islamic banks in Indonesia for the period 2014-2018. The sampling method used was purposive sampling from 12 Islamic banks met the criteria to be the sample. The method of analysis used in this study is multiple linear regression. The results showed by model-1 that intellectual capital measured by human capital efficiency (HCE), structural capital efficiency (SCE) and capital employed efficiency (CEE) and GCG measured by board size (BS) and board of demography (BD) simultaneously are having significant influence to the return on assets (ROA) of the banks. The results showed by model-2 that intellectual capital measured by human capital efficiency (HSE), structural capital efficiency (SCE) and capital employed efficiency (CEE) and GCG measured by board size (BS) and board of demography (BD) simultaneously are having non-significant influence to the assets growth (AG) of the banks.